Kerukunan dan Toleransi Antar Umat Beragama - Artis Artis (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2011)
Harmony and tolerance is necessary to be implanted in every human, because humans as social beings not be separated from others. Harmony and tolerance that needs to be fostered not only on inter-cultural but including religion. Every religion has different beliefs, therefore, each religion can maintain and nurture his people to maintain communal harmony and mutual respect and keep the things that sara is to avoid conflicts between religions for the sake of maintaining peace in the frame of national unity and stateless